Relationship between quality service determinants with the quality of cleaning service - Umi Nur Ai'syah , Zulkefli (2014)
Quality of Cleaning Service is an important essence in Cleaning Service Industry. Customers Satisfaction is often used as the evaluation method to determine the quality of cleaning service. Customer satisfaction is depends on the element of customers expectation and perception of quality which can be divided into four main determinants which is Functional Quality, Technical Quality, Process Quality and Aesthetic Quality. Therefore, this paper intends to identify the relationships of quality determinants and the quality of cleaning service as well as its dominant factor. So, the respondents targeted for this project is staffs that work in office in UMP Gambang. Questionnaires were distributed and collected. For the analysis performed on the gathered data, the study shows that there is correlation of quality determinants with the quality of cleaning service